Experimental Studies on Venous Thrombosis: Effect of Coagulants, Procoagulants and Vessel Contusion - Aronson, David L; Thomas, Duncan P (Thrombosis and Haemostasis, 1985)
We have examined the relative contribution of stasis, activated coagulants, procoagulants and vessel wall damage in the pathogenesis of experimental venous thrombosis. Using a Wessler stasis model in rabbits, we found an inverse correlation between duration of stasis and the amount of Contact Factor and Factor Xa required to produce a stasis thrombus. However, the slope of the dose-response curve for producing thrombi was different with these two coagulants. The infusion of Factor IX complex was also thrombogenic in this model despite prolonged circulation prior to stasis, implying that high levels of multiple procoagulants may be thrombogenic. In contrast, Factor VIII concentrates or a purified Factor IX preparation did not give thrombi under these conditions.When the vessel wall was crushed mechanically, followed by restored blood flow and subsequent stasis, there was essentially no formation of thrombi over the time course of the experiments. Scanning electron microscopy demonstrated that although the endothelium was swollen and damaged, there was usually no exposure of sub-endothelium and no adherence platelets. Where there was definite disruption of the endothelium, activated platelets could be seen adhering to the vessel wall. However, the blood in the segments remained fluid over a period of 30 min, despite the presence of adherent platelets.Our experiments demonstrated that the combination of vessel wall damage and stasis was relatively ineffective in producing venous thrombosis. In contrast, high levels of zymogens or small amounts of activated clotting factors, combined with local stasis, is a very effective thrombogenic stimulus in the venous system.
Keywords: Experimental venous thrombosis; Factor Xa; Contact factor; IX complex; Vessel wall